2021
DOI: 10.3389/fphar.2021.725268
|View full text |Cite
|
Sign up to set email alerts
|

MLIF Modulates Microglia Polarization in Ischemic Stroke by Targeting eEF1A1

Abstract: Monocyte locomotion inhibitory factor (MLIF) is a heat-stable pentapeptide from Entamoeba histolytica. Our previous study found that MLIF protects against ischemic stroke in rats and mice and exerts a neuroprotection effect in human neuroblastoma SH-SY5Y cells. Microglia/macrophage polarization has been proven to be vital in the pathology of ischemic stroke. Nevertheless, whether MLIF is able to modulate microglia/macrophage polarization remains unclear. We performed middle cerebral artery occlusion (MCAO) on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…Compared with the vehicle group, selective sEH inhibitor‐treated rats showed a reduction in M1 monocyte/macrophage activation and proinflammatory mRNA expression in the infarct cortex of rats ( 41 ). Similar results were found in another study, while the authors delivered MLIF (monocyte locomotion inhibitory factor, a pentapeptide known to play anti‐inflammatory effects) to rodents with IS, and found increased M2 transformation from M1 phenotype, which was related with better behavioral performance and smaller infarcted area ( 42 ).…”
Section: The Activation and Differentiation Of The Mps ...supporting
confidence: 81%
See 1 more Smart Citation
“…Compared with the vehicle group, selective sEH inhibitor‐treated rats showed a reduction in M1 monocyte/macrophage activation and proinflammatory mRNA expression in the infarct cortex of rats ( 41 ). Similar results were found in another study, while the authors delivered MLIF (monocyte locomotion inhibitory factor, a pentapeptide known to play anti‐inflammatory effects) to rodents with IS, and found increased M2 transformation from M1 phenotype, which was related with better behavioral performance and smaller infarcted area ( 42 ).…”
Section: The Activation and Differentiation Of The Mps ...supporting
confidence: 81%
“…Additionally, the blockade of adrenergic activity significantly reversed these cytokine levels and improved neurological results (73). Rajan Liu et al (42) inflammatory changes in the CNS of patients. Hints could only be illustrated from studies of peripheral immune changes in IS patients.…”
Section: Inflammation Regulationmentioning
confidence: 99%
“…Values are mean ± SD, # P < 0.05 compared with Sirt3 f/f group, + P < 0.05 compared with ICH + IF + Vehicle group microglia is to engulf RBCs and remove cellular debris [31]. Under certain conditions, microglia can also express arginase1 (Arg1), insulin-like growth factor (IGF-1), Ym1 and anti-inflammatory cytokines, such as IL-10 and IL-4, which facilitate recovery of CNS injury including ischemic stroke [32]. Considering the high plasticity of microglia according to different pathologic events or microenvironments [33], deeper insight into the regulatory mechanisms of microglial phenotype variations may help maintain the homeostasis of microglia activation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that EEF1A1 and Cag A synergistically regulate IL-6 expression by impacting the activation of p-STATS727 in the cell nucleus [12]. Yulan Liu et al [13] found that EEF1A1 may have a signi cant role in moderating microglia polarization. These reports indicate that EEF1A1 may be essential in regulating in ammatory processes.…”
Section: Introductionmentioning
confidence: 99%